Diagnosis of Invasive Aspergillosis in Hematological Malignancy Patients: Performance of Cytokines, Asp LFD, and Aspergillus PCR in Same Day Blood and Bronchoalveolar Lavage Samples - Heldt, Sven (J Infect, 2018)
BACKGROUND: Aspergillus spp. induce elevated levels of several cytokines. It remains unknown whether these cytokines hold value for clinical routine and enhance diagnostic performances of established and novel biomarkers/tests for invasive aspergillosis (IA). METHODS: This cohort study included 106 prospectively enrolled (2014–2017) adult cases with underlying hematological malignancies and suspected pulmonary infection undergoing bronchoscopy. Serum samples were collected within 24 hours of bronchoalveolar lavage fluid (BALF) sampling. Both, serum and BALF samples were used to evaluate diagnostic performances of the Aspergillus-specific lateral-flow device test (LFD), Aspergillus PCR, β-D-glucan, and cytokines that have shown significant associations with IA before . RESULTS: Among 106 cases, 11 had probable IA, and 32 possible IA; 80% received mold-active antifungals at the time of sampling. Diagnostic tests and biomarkers showed better performance in BALF versus blood, with the exception of serum interleukin (IL)-8 which was the most reliable blood biomarker. Combinations of serum IL-8 with either BALF LFD (sensitivity 100%, specificity 94%) or BALF PCR (sensitivity 91%, specificity 97%) showed promise for differentiating probable IA from no IA. CONCLUSIONS: High serum IL-8 levels were highly specific, and when combined with either the BALF Aspergillus-specific LFD, or BALF Aspergillus PCR also highly sensitive for diagnosis of IA.